Arsenic Exposure, Dermatological Lesions, Hypertension, and Chromosomal Abnormalities among People in a Rural Community of Northwest Iran - Dastgiri, Saeed; Mosaferi, Mohammad; Fizi, Mohammad AH; Olfati, Nahid; Zolali, Shahin; Pouladi, Nasser; Azarfam, Parvin (Journal of Health, Population and Nutrition, 2010)
Chronic exposure to arsenic compounds is one of the major public-health problems in many developing and some developed countries. The aim of this study was to investigate the effects of chronic exposure to arsenic on dermatological lesions, hypertension, and chromosomal abnormalities among people in a community in the northwest of Iran. The occurrence of dermatological lesions, hypertension, and chromosomal abnormalities was investigated in two groups: Ghopuz village, including 101 subjects with chronic exposure to arsenic in drinking-water and Mayan village, including 107 subjects with no exposure. Daily/ yearly absorbed amounts of arsenic were calculated for all subjects. Cumulative arsenic index for each individual was then estimated on the basis of age, water consumption, and location of residence. Arsenic concentration in drinking-water sources in Ghopuz and Mayan villages was 1031±1103 μg/L and non-detectable respectively. The mean systolic blood pressure in the exposure group [n=137, 95% confidence interval (CI 132-142)] was significantly higher than that in the control group (n=107, 95% CI 99.9-114). A similar significant difference was observed for diastolic blood pressure (exposed: n=82, 95% CI 79-85 vs non-exposed: n=71, 95% CI 66-75). The incidence of hyperkeratosis was 34 times higher among the exposure group compared to the control subjects [odds ratio (OR)=34, p<0.001)]. A significant difference was also observed in the occurrence of skin-pigmentation between the two groups (OR=2.4, p<0.007). Location and severity of the pigmentations were statistically different between the two groups. Twenty-five percent of the subjects in the exposure group showed chromosomal abnormalities (p=0.05). Arsenic exposure was a serious health problem in the region. More studies are needed to investigate the long-term effects and doseresponse relationship of arsenic in the region and similar areas. Wide-ranging monitoring programmes for drinking-water sources should be implemented by public-health authorities. Key words: Arsenic; Cross-sectional studies; Dermatological lesions; Hypertension; Chromosomal abnormalities; Water pollution; Water supply; Iran DOI: 10.3329/jhpn.v28i1.4519 J Health Popul Nutr 2010 Feb; 28(1): 14-22